KESEIMBANGAN KEHIDUPAN KERJA DALAM MENJALANKAN PERAN GANDA STUDI PADA MAHASISWA UNIVERSITAS PAMULANG - Wiyanto Wiyanto (Inovasi, 2021)
It is a challenge for each individual who carries out more than one concurrent role in his life (Dual Role) as experienced by Pamulang University Students. Roles need to be aligned and strategies need to be implemented to avoid problems. Problems such as work, family and college conflicts have the potential to occur. This study aims to determine work, family and college conflicts and explore various strategies to overcome conflicts used by Pamulang University students in carrying out multiple roles. Qualitative research methods were used for this research. Data were collected through interviews and questionnaires. Respondents who became the subject of this study were determined through three criteria. The collected data were analyzed and concluded. Research results Work, family and college conflicts experienced by Pamulang University students are caused by pressure in lectures such as, lecture materials, coursework, lecture time, time to do college assignments, tuition fees, missing lecture information, forgetting to do college assignments, problems knowledge. While the pressure at work such as, a lot of work volume, complex work that requires extra brain performance, short time to complete work, infrastructure that is considered lacking, the presence of a leader who does not fit, co-workers who are less comfortable, canteen menus that are considered inadequate. expensive. In addition, the dual roles that are carried out simultaneously also cause their own pressure, for example the pressure to complete work and college assignments at the same time. Various strategies taken by students in carrying out multiple roles in order to minimize conflict and even to resolve conflicts and can lead students to achieve the desired goals. The strategy adopted is adjusted to the type of conflict that exists. Every conflict, pressure requires resolution separately or not the same between one pressure with another pressure.Keywords : Work Life Balance, Multiple Roles